Character Education Management at Islamic Grassroot Education: The Integration of Local Social and Wisdom Values - Arif, Arifuddin M; Nurdin, Nurdin; Elya, Elya (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
This study examined the implementation of character within grassroots Islamic education institutions that integrate local customs values in Palu City, Central Sulawesi. This study explores the strategy of character education implementation at the grassroots Islamic education institutions level and provides insight into the body of knowledge and practitioners. The study was conducted with a qualitative method. The data was gathered through field observation, focus group discussion, in-depth interviews, and written document analysis. In addition, in-depth interviews were conducted with elementary school teachers, parents, and the city Education and Culture Department officials. The findings show that the Palu city Department has implemented the education character program by aligning the character education programs with their vision. Character education programs have also been implemented through the cultured Thursday parade, family involvement through Paguyuban, and students' immersion into local culture and wisdom values. We concluded that implementing education characters within Basic Islamic education institutions had increased early-age students' awareness of tolerance, respect, and mutual understanding of characters based on local culture and wisdom values by Islamic teaching within the city, dominated mainly by immigrants from different ethnic in Indonesia.